2020
DOI: 10.1093/ndt/gfaa131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiovascular risk stratification strategies in kidney transplantation over time

Abstract: Background Kidney transplant recipients exhibit a dramatically increased cardiovascular (CV) risk. In 2007, Austrian centres implemented a consensus of comprehensive CV screening programme prior to kidney transplantation (KT). The consensus placed a particular emphasis on screening for coronary artery disease (CAD) with cardiac computed tomography (CT) or coronary angiography (CAG) in patients with diabetes mellitus, known CAD or those having multiple conventional CV risk factors. Here, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…We conducted a single-center retrospective cohort study of 376 consecutive KTRs transplanted at the Transplant Center Graz (Medical University of Graz) from 1 January 2005 to 31 December 2015. Patients with concomitant serum Mg 2+ and 25(OH)-vitamin D measurement within three months after KT were identified using our database as published previously ( Figure 1 ) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted a single-center retrospective cohort study of 376 consecutive KTRs transplanted at the Transplant Center Graz (Medical University of Graz) from 1 January 2005 to 31 December 2015. Patients with concomitant serum Mg 2+ and 25(OH)-vitamin D measurement within three months after KT were identified using our database as published previously ( Figure 1 ) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…All data were derived retrospectively from the KT and electronic medical records of our center and the Austria Dialysis and Transplantation Registry (OEDTR), as stated previously [ 20 ]. The date of KT (index date) was registered for the calculation of time to outcome event.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no other RCTs examining whether more screening for asymptomatic coronary artery disease in prospective KTR improves survival or reduces CV events after transplantation, two important observational studies have reported recently. An intensive CV risk stratification protocol implemented nationwide in Austria in 2007 resulted in over 50% of transplanted patients having a coronary angiogram but failed to demonstrate any improvement in patient survival or a reduction in coronary events in patients transplanted directly after (2008–11) or 5 years after (2012–15) compared with historical data (2003–07) [ 31 , 33 ]. A prospective study of 2572 UK KTR who received a transplant in 2011–17 in 18 centres found that 51% underwent cardiac screening pre-transplantation with screening by centre varying from 5% to 100% [ 32 ].…”
Section: Value Of Revascularization In Stable Ischaemic Heart Diseasementioning
confidence: 99%
“…This is more than a theoretical consideration. For example, during the implementation of a ‘stricter’ CV screening process in Austria, the median age and prevalence of comorbidities of KTRs in that country were unchanged over a 13-year observation period [ 31 ]. Elsewhere, international trends were those of an ageing KTR population [ 70–74 ].…”
Section: Evidence That Conventional Approach To Cardiac Screening Causes Harmmentioning
confidence: 99%